Аналіз конструкцій запобіжників з елементами з пам’яттю форми - Грищук, Юрій Степанович; Мележик, Ю. М. (НТУ "ХПІ", 2008)
Проведено огляд і аналіз конструкцій та принципи дії запобіжників з елементами з пам’яттю форми, виявлені їх конструктивні особливості, недоліки, переваги і доцільність їх застосування для покращення техніко-економічних характеристик швидкодіючих запобіжників (ШЗ).

Review and analysis of safety fuses with form memory, their constructions and principles of action are resulted. Their design features, lacks, advantages and expediency of their application for modernization of the electromagnetic drive and improvement of its technical and economic characteristics in high-speed safety fuses are revealed.
Application of substances with form memory in meltable elements of fast fuses
Keywords: швидкодіючі запобіжники; ШЗ; ЗПФ; термочутливий елемент; приводний елемент; струм